Caracterização do perfil eletroforético de isoenzimas do metabolismo intermediário de triatomíneos (Hemiptera, Reduviidae) com algumas considerações sobre sua ecologia alimentar - Almeida, Josimar Ribeiro de (1980)
In this work isoenzymes electrophoretic spots of oxidoredutases, transferases and hydrolases, and general proteins, in the haemolymph of Triatominae bugs: belonging to the genera Triatoma, Panstrongylus and Rhodnius were analysed. Enzimatic activity of ODH, ADH, MDH, GAL . DH, SOR. DH, AcPh, AiPh, IPO, LAP, alfa and beta EST in these bugs were observed. The results s how that there is usually monomorphism in the oxidoredutases and transferases systems. But in hydrolases' class 3. 1, polymorphism in R. prolixus for one locus wich allels we called R (quickly), M (rniddle) and L (sowly) were detected. There are 6 possible different phenotypes as a consequence of various arrangements with 3 alleles. The sexual dimorphism and age do not alter the electrophoretic pattern. Alimentation in different hosts does not produce qualitative variations in the electrophoretic patterns of the isoenzymatic systems analized.